Anti‐platelet factor 4/heparin antibodies in patients with impaired graft function after liver transplantation. (June 2014) - Bakchoul, T.; Assfalg, V.; Zöllner, H.; Evert, M.; Novotny, A.; Matevossian, E.; Friess, H.; Hartmann, D.; Hron, G.; Althaus, K.; Greinacher, A.; Hüser, N.
Summary Background Heparin, the standard perioperative anticoagulant for the prevention of graft vessel thrombosis in patients undergoing liver transplantation (LT), binds to the chemokine platelet factor 4 (PF4). Antibodies that are formed against the resulting PF4/heparin complexes can induce heparin‐induced thrombocytopenia. LT is a clinical situation that allows the study of T‐cell dependency of immune responses because T‐cell function is largely suppressed pharmacologically in these patients to prevent graft rejection. Objectives To investigate the immune response against PF4/heparin complexes in patients undergoing LT. Patients and Methods In this prospective cohort study, 38 consecutive patients undergoing LT were systematically screened for anti‐PF4/heparin antibodies (enzyme immunoassay and heparin‐induced platelet aggregation assay), platelet count, liver function, and engraftment. Results At baseline, 5 (13%) of 38 patients tested positive for anti‐PF4/heparin IgG (non‐platelet‐activating) antibodies. By day 20, an additional 5 (15%) of 33 patients seroconverted for immunoglobulin G (two platelet‐activating) antibodies. No patient developed clinical heparin‐induced thrombocytopenia. Two of six patients with graft function failure had anti‐PF4/heparin IgG antibodies at the time of graft function failure. Graft liver biopsy samples from these patients showed thrombotic occlusions of the microcirculation. Conclusions Anti‐PF4/heparin IgG antibodies are generated despite strong pharmacologic suppression of T cells, indicating that T cells likely have a limited role in the immune response to PF4/heparin complexes in humans.